The link between hepatitis C virus and diabetes mellitus: Improvement in insulin resistance after eradication of hepatitis C virus. Issue 3 (6th April 2018) - Hum, Justine; Jou, Janice H.
Abstract : Watch a video presentation of this article Watch the interview with the author